The recorded evidence of AD 1755 Atlantic tsunami on the Gibraltar coast - Rodríguez-Vidal, J.; Cáceres, L. M.; Abad, M.; Ruiz, F.; González-Regalado, M. L.; Finlayson, C.; Finlayson, G.; Fa, D.; Rodríguez-Llanes, J. M.; Bailey, G. (Journal of Iberian Geology, 2011)
Evidence of the AD 1755 tsunami consisting of the same type of accretions produced by the re-deposition of earlier sediments, has been recorded at three different height along the coast of Gibraltar: Along a shallow sandy shore, the tsunami wave reached a run-up of 2–3 m, whereas along steep, cliff–lined shores (Rosia Bay) it surpassed 5 m. An overwash deposit was also identified at the bottom of a lagoon (The Inundation), at 0.5 m b.s.l., on the isthmus that joins the Rock with the mainland. Southern submerged platforms (Vladi’s Reef) were also affected by the erosional backwash to a depth of 22 m. The tsunamigenic sediments exhibit a bimodal granulometry, mainly composed of sands with a coarser fraction composed of marine faunal shells remains, together with larger clasts derived from the rocky substrate. All remobilized sediments were dated by historical methods and radiocarbon dating.
Keywords: Lisbon earthquake; AD 1755 tsunami; run-up; sedimentary record; radiocarbon dating; Gibraltar